Mapping a sustainable water future: private sector opportunities for global water security and resilience - Green, P. A.; Vörösmarty, C. J.; Koehler, D. A.; Brown, C.; Rex, William; Osuna, V. R.; Tessler, Z. (Elsevier, 2024)
Water security remains a critical global development challenge, compounded by persistent public funding shortfalls. Society urgently needs to identify opportunities for innovative private sector engagement in water security solutions. To identify feasible and impactful solutions, quantitative tools are needed to delineate complex environmental and socioeconomic water challenges and prioritize private sector investment opportunity spaces to address these challenges. We introduce the first global and regional-scale maps showing where threats to water security coincide with private sector opportunities to address them. The successful deployment of water solutions is contingent upon the societal and governance landscape that underpins a nation’s capacity to support sustainable water threat interventions and water-related business activities. By delineating areas with substantial pressures on water resources and assessing nations’ enabling environments to support private sector investments, we find nearly two-thirds of the world’s population could benefit from private sector interventions today, with middle income countries realizing the greatest benefits. In the face of global economic development and climate change, such solutions will become increasingly essential in future decades.